Courageous decision making in public organizations: the roles of ethical leadership and dynamic capabilities - Shamim, Saqib; Schwarz, Gary; Rahman, Mushfiqur; Rehman, Wali Ur (Taylor & Francis, 2026)
Public-sector employees frequently need to make difficult decisions that may go against powerful stakeholders. Such choices often involve personal and professional risks and require courage from decision makers. This study operationalizes Kelman and colleagues’ (2016) courageous decision-making construct and examines the relationship between ethical leadership and ethically motivated courageous decision making. Courageous decision making is particularly crucial in bureaucratic public organizations that face institutional voids. By analyzing multi-wave and multi-level data from 289 police officers and their 45 direct supervisors in Bangladesh, we found that ethical leadership influences courageous decision making through the mediation effects of ethics-focused dynamic capabilities (DCs). We advance the understanding of ethics-focused DCs by proposing a comprehensive framework aligned with the core dimensions of DCs (i.e., sensing, seizing, and transforming capabilities). We also show that employees’ public service motivation moderates the relationship between ethical leadership and ethically motivated courageous decision making.
Keywords: fi=InnoLab|en=InnoLab|